Revitalisasi Tafsir Maudu’i untuk Dakwah di Era Media Baru: Revitalization oaf Thematic Qur’anic Exegesis for Da’wah in the New Media Era - Ulumudin, Ihya'; Satuyar, Satuyar (Institut Agama Islam Syarifuddin Lumajang, 2025)
Islamic da’wah in the digital era faces significant methodological challenges: religious messages are now packaged in fast, visual formats—snackable content—that often sacrifice the depth of Qur’anic interpretation. Many popular contents employ Qur’anic verses thematically but lack strong exegetical methodology, leading to potential meaning reduction and oversimplification (Hasanah et al., 2022). This study aims to explain the relevance of Tafsir Maudu’i-a systematic thematic exegesis method-within the context of new media da’wah and to formulate effective revitalization strategies. A descriptive qualitative approach was employed, using literature studies on classical and contemporary exegesis (Al-Farmawi, 1978; Yusuf, 2021) as primary data, and digital observations of popular da’wah content (YouTube, TikTok) as secondary data. The data were analyzed through content analysis to compare methodological adherence with digital communication practices. The results indicate that Tafsir Maudu’i possesses high contextual flexibility, making it ideal for addressing modern social issues while upholding the principles of wasathiyyah (moderation) and maqasid al-shari‘ah (objectives of Islamic law). However, the new media format’s demand for speed often conflicts with the exegetical requirement for deep contextual analysis. As a solution, the study identifies three revitalization strategies: (1) procedural application of the Tafsir Maudu’i framework within content workflows; (2) formal collaboration between exegetical scholars and content creators; and (3) development of micro-tafsir formats (e.g., thematic infographics). The main contribution of this study lies in proposing a new methodological framework that integrates the rigor of classical exegesis with the efficiency of modern communication, emphasizing that strengthening Qur’anic literacy among digital da’i is essential to ensure viral content remains theologically accurate.